Prevalence and Correlates of Truancy among School-Going Adolescents in Mozambique: Evidence from the 2015 Global School-Based Health Survey - Abdul-Aziz Seidu (The Scientific World Journal)
This study examined the prevalence of truancy and its associated factors among 1500 school-going adolescents using the 2015 Mozambique Global School-based Student Health Survey data. The association was assessed using bivariate (Chi square) and multivariate (logistic regression) analysis. The prevalence of truancy was 36.6% (38.4% of males and 35.1% of females). It was found that adolescents aged 15 years and older [OR=1.460,95% CI=1.153,1.848], experiencing hunger [OR=1.613 95% CI= 1.051,2.475], current tobacco use [OR=1.613 95%CI=1.051,2.475], being bullied [OR=1.314, 95% CI=1.027,1.681], facing an attack, smoking [OR= 1.893, 95% CI=1.293,2.771], having 1-2 close friends [OR=1.656, 95% CI=1.276,2.14], and feeling lonely [OR=1.295, 95% CI=1.019,1.646] were the factors that predisposed adolescents to truant behaviour. Conversely, parental supervision [OR=0.53, 95% CI=0.232,0.791] was a protective factor against truancy. There is the need to design school-based interventions aimed at reducing truancy in Mozambique by tackling the predisposing factors and encouraging the protective factors.